2019
DOI: 10.1111/jgh.14600
|View full text |Cite
|
Sign up to set email alerts
|

Modified non‐flared fully covered self‐expandable metal stent versus plastic stent for preoperative biliary drainage in patients with resectable malignant biliary obstruction

Abstract: Background and Aim Fully covered self‐expandable metal stents (FCSEMS) may be better than plastic stents (PS) for preoperative biliary drainage (PBD) to relieve cholangitis or jaundice for resectable malignant biliary obstruction (MBO). However, modification of current FCSEMS designed originally for nonresectable MBO is needed to be a proper stent for PBD. The aim of this study was to evaluate the possible superiority of non‐flared modified FCSEMS (M‐FCSEMS) with 12‐mm diameter and waist of central portion ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…No differences were found in overall preoperative complications and postoperative outcomes between the 2 groups 47 . A more recent RCT also showed similar results 48 . In patients undergoing neoadjuvant therapy, SEMS also provides longer stent patency and less need for reintervention compared with PS 49,50 .…”
Section: Biliary Stentingmentioning
confidence: 57%
See 1 more Smart Citation
“…No differences were found in overall preoperative complications and postoperative outcomes between the 2 groups 47 . A more recent RCT also showed similar results 48 . In patients undergoing neoadjuvant therapy, SEMS also provides longer stent patency and less need for reintervention compared with PS 49,50 .…”
Section: Biliary Stentingmentioning
confidence: 57%
“…47 A more recent RCT also showed similar results. 48 In patients undergoing neoadjuvant therapy, SEMS also provides longer stent patency and less need for reintervention compared with PS. 49,50 Although an RCT showed that FC-SEMS had longer stent patency duration and fewer days of neoadjuvant therapy delay compared with PS and uncovered (U) SEMS, 51 another RCT showed noninferiority of U-SEMS versus FC-SEMS on achieving sustained biliary drainage.…”
Section: Extrahepatic Biliary Obstructionmentioning
confidence: 99%
“…On the other hand, for PBD, the choice of the optimal stent remains controversial. SEMSs are thought to be preferable for cases where the wait time for surgery is relatively long, for example, NAC cases (the wait time for surgery is 3–6 months) 14–24 . However, from meta‐analyses comparing SEMSs with PSs for PBDs, the rate of post‐endoscopic retrograde cholangiopancreatography pancreatitis (PEP) has been reported to be higher for patients receiving SEMSs than that for those receiving PSs 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…SEMSs are thought to be preferable for cases where the wait time for surgery is relatively long, for example, NAC cases (the wait time for surgery is 3–6 months). 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 However, from meta‐analyses comparing SEMSs with PSs for PBDs, the rate of post‐endoscopic retrograde cholangiopancreatography pancreatitis (PEP) has been reported to be higher for patients receiving SEMSs than that for those receiving PSs. 25 , 26 PEP can interfere with the beginning of NAC and cause adhesion around the pancreas causing difficulties during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Intraductal placement of stents (i.e., placement above the duodenal papilla) can reduce duodenobiliary reflux, and may thereby achieve longer stent patency durations, lower occlusion and late adverse events rates. 10,11 If endoscopic sphincterotomy (ES) is not performed, these benefits may be more pronounced. Furthermore, avoiding ES seems to prevent stent migration as stents are unlikely to pass through the duodenal papilla in the absence of ES.…”
Section: Introductionmentioning
confidence: 99%